Development of a System for Submitting Funds Proposals at the National Web-Based University: Development of a System for Submitting Funds Proposals at the National Web-Based University - Bimo Anggoro Seno; Septi Andryana; Agus Iskandar (Jurnal Mantik, 2020)
The development of the digitalization of several activities, led the National University in the development of a planned information management system for the benefit of student associations. The difficulty of student associations in submitting proposals and activity reports, has hampered and consumed a lot of time. The process of validating proposals and reporting activities through several parties is also one of the obstacles. Therefore it is necessary to realize a web-based information management system that makes it easy for them in this regard. This development is intended to facilitate the student association in submitting proposals and reporting the results of activities. Not only students, some related parties such as student bureaus, vice deans, lecturers can also be facilitated by this system. The waterfall method has been applied in the development of this web-based system. The results in the form of web-based systems have gone through the stages of limited trials and periodic system maintenance. A system that is fully functional, dynamic, and efficient in use has provided a good guarantee to facilitate the collection of proposals and other activities. The relevance of this article lies in the fact that as technological dynamics change, software development will evolve in several aspects of life. The ease with which this information system has been generated has minimized the energy, time, and finances of Unas student associations in carrying out procurement procedures and reporting activities